RELEVANCE OF THE IMPLEMENTATION AND RESPONSE OF SHARIA ECONOMY IN THE DIGITALIZATION OF E-COMMERCE TRANSACTIONS IN INDONESIA - Amelty Lisa; Siti Afidatul Khotijah; Bobur Sobirov (IAIN Batusangkar, 2022)
The purpose of this paper is to analyze how Islamic economics views and responds to the increasingly rapid development of digitalization, especially transactions that occur in on-line buying and selling or commonly referred to as e-commerce as well as to find out where the application of Islamic economics in e-commerce business activities is and to find out and clarify the validity of transactions that occur whether it is permissible and legal if transactions are carried out on the internet network in the form of e-commerce. This research uses the Library Research method or can also be called library research, meaning that the data source for this research is based on a literature review that comes from theses, scientific works, journals, news, and several sources that are relevant and support the discussion in this research. After analyzing some of the data that has been obtained, the researcher can conclude that e-commerce transactions are allowed and legitimate if they are carried out in accordance with the rules and regulations of Islamic law. In this case, it can also be concluded that the Islamic economy responds to the development of digitalization very positively. This is marked by the fact that Islam does not close itself off from the advancement of digitalization in on-line business because as a result of this progress, it has a positive influence on both the perpetrators and the Islamic economy itself.